How Can We Decide? When Ought a Person with Disabilities Be Moved from Their Home to Full-Time Residential Care? - Shrier, Paul (Journal of disability & religion, 2021)
A family member with disabilities is usually moved to full-time residential care when a crisis occurs in the home. Alternatively, this paper creates criteria to decide if a family member ought to be moved before a crisis occurs. The quality of relationships in the home and the likelihood that crises will occur are determined by both caregiver mental health and the behaviors of the person with disabilities. Improving caregiver mental health can keep more persons with disabilities at home. A biopsychosocial-spiritual model of healthcare, John Wesley’s sermon “On Family Religion,” and caregiver health research are used to construct effective criteria.